Graft Detachment Pattern After Descemet Membrane Endothelial Keratoplasty Comparing Air Versus 20% SF6 Tamponade. Issue 7 (July 2018) - Siebelmann, Sebastian; Lopez Ramos, Sebastian; Scholz, Paula; Matthaei, Mario; Schrittenlocher, Silvia; Heindl, Ludwig M.; Bachmann, Björn; Cursiefen, Claus
Abstract : Purpose: The change from air to 20% sulfur hexafluoride (SF6 ) as anterior chamber tamponade for Descemet membrane endothelial keratoplasty (DMEK) significantly reduced the rebubbling rate. Nonetheless, underlying mechanisms are not completely understood. In this study, we investigate the morphology of graft detachments after DMEK depending on the tamponade and its influence on postoperative rebubbling. Methods: In this retrospective analysis of prospective data of 204 consecutive patients who underwent DMEK with 100% air, or 20% SF6, we compared the SF6 group with the air group regarding the number, lateral and axial diameter and localization of detachments, visual acuity (BSCVA), and incidence of rebubbling after 1 week (T1), after 1 (T2), 3 (T3), 6 (T4), and 12 (T5) months postoperatively. Results: The air group showed more detachments at all time points. Detachments in this group were of a larger axial diameter at T1, T4, and T5 and of a larger lateral diameter at T1, T3, T4, and T5 compared with the SF6 group. Patients receiving SF6 needed fewer rebubblings at T1 compared with patients receiving air (12.1% vs. 29.1%, P = 0.003), but not at T2 (15.1% vs. 19.1%, P = 0.56). There was no difference in postoperative BSCVA between the groups. Conclusions: Early graft attachment after DMEK, which is improved by the use of SF6 as anterior chamber tamponade, is important for the overall rebubbling rate and improves wound-healing mechanisms between the graft and recipient cornea. Faster resolving air tamponade is associated with extended detachments especially inferiorly and mid-peripherally, but has no negative effect on the long-term BSCVA. Abstract : Supplemental Digital Content is Available in the Text.